Effects Of Organic Liquid and Inorganic Fertilizers on Tomato Yield in The Central Rift Valley of Ethiopia - Hordofa Sigaye, Melkamu (Sustainability Science and Resources, 2024)
This study investigates the effects of organic liquid fertilizers and inorganic fertilizers on tomato yield in the Central Rift Valley of Ethiopia, addressing the significant yield gap between Ethiopian tomato production. Results indicate that the application of combination of 100% recommended nitrogen and phosphorus with either 60 ha⁻¹ and 45L ha⁻¹ organic liquid fertilizer significantly increased tomato marketable and total yields at all locations, with the highest yield observed at Sankura (50.36 t ha-1), Hawassa (46.6 t ha-1) and Koka (36.7 t ha-1). However, as the inorganic nitrogen-phosphorus application decreased below 100% can decline tomato yields at all sites. From an economic standpoint, applying 100% RNP without OLF yielded the best marginal rate of return (MRR). Additionally, the combination of 100% RNP with 60 L ha⁻¹ of OLF not only demonstrated substantial yield advantages but also proved to be profitable. Based on financial considerations, the sole application of 100% RNP and its integration with 60 L ha⁻¹ OLF best show a higher yield than the rest of the treatments. Therefore, the findings suggest that both approaches are recommended for optimizing tomato production in the central Rift Valley of Ethiopia, with the choice depending on farmers’ financial capacity and long-term soil health considerations.